PENINGKATAN KEMAMPUAN KOGNITIF MELALUI PEMANFAATAN BARANG BEKAS PADA ANAK KELOMPOK A DI RA NURUL QOMARIAH BOKOR PAGEDANGAN TUREN-MALANG - Kustinuk; Afifatu Rohmawati (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2019)
The limited of facilities and infrastructure available in the scope of schools can cause children to not be able to explore broadly. The purpose of the study was to describe cognitive abilities through the use of used items for group A children. Classroom action research (CAR) method uses two cycles in its application. Data collection techniques through observation, interviews, and documentation. The findings in the study there are percentages of 52.5%. The value is reinforced from the results of filling out a simple questionnaire by students that reflects a sense of pleasure. There are 21 children, 9 children with a percentage of 42.86% said they were happy. Meanwhile, 12 children with a percentage of 57.41% expressed very pleased with the different learning activities. This study can be concluded that the results of the study appear to greatly improve the cognitive abilities of children. This is marked by an increase in the average results of the development of the ability of students to recognize shapes, colors, classifying objects, and sorting through innovation in the use of used goods.